Emotional distress and well-being among people with motor neurone disease (MND) and their family caregivers: a qualitative interview study - Lucy Yardley; Adam W A Geraghty; Cathryn Pinto; Laura Dennison (BMJ Open)
Objective We aimed to get an in-depth understanding of the emotions experienced by people with motor neurone disease (MND) and their caregivers, and to explore what impacts emotional distress and well-being.Design Qualitative study using semi-structured interviews with people with MND and caregivers.Setting Participants were recruited from across the UK and took part in interviews conducted either face to face, by telephone or email to accommodate for varying levels of disability.Participants 25 people with MND and 10 caregivers took part. Participants were purposively sampled based on their MND diagnosis, symptoms and time since diagnosis.Data analysis Data were analysed using inductive reflexive thematic analysis.Results Eight broad themes were generated (20 subthemes). Participants described the emotional distress of losing physical function and having a threatened future because of poor prognosis. Keeping up with constant changes in symptoms and feeling unsupported by the healthcare system added to emotional distress. Finding hope and positivity, exerting some control, being kinder to oneself and experiencing support from others were helpful strategies for emotional well-being.Conclusion The study provides a broad understanding of what impacts emotional distress and well-being and discusses implications for psychological interventions for people with MND and caregivers. Any communication and support provided for people with MND and their caregivers, needs to pay attention to concepts of hope, control and compassion.